2014
DOI: 10.1016/j.ijsu.2013.12.012
|View full text |Cite
|
Sign up to set email alerts
|

T1 colorectal cancer: Poor histological grading is predictive of lymph-node metastases

Abstract: Poor differentiation was the only independent significant predictor of nodal involvement in pT1 colorectal tumours. Our and literature's data confirm that risk factors must be prospectively collected and reported; further genetic and epigenetic predictive factors have to be investigated in order to carefully evaluate the needing of major surgery for pT1 colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
3
10
1
Order By: Relevance
“…In terms of clinical features, our study found that age, M stage, preoperative CA19-9 level, preoperative CEA level, tumor size and pathological grading were independent risk factors associated with LNM in CRC patients, which is consistent with the findings of previous studies [8,[20][21][22]. Among the five potential clinical risk factors, the preoperative CA19-9 level and preoperative CEA level have been considered clinical indicators closely related to the LNM of CRC [20].…”
Section: Discussionsupporting
confidence: 90%
“…In terms of clinical features, our study found that age, M stage, preoperative CA19-9 level, preoperative CEA level, tumor size and pathological grading were independent risk factors associated with LNM in CRC patients, which is consistent with the findings of previous studies [8,[20][21][22]. Among the five potential clinical risk factors, the preoperative CA19-9 level and preoperative CEA level have been considered clinical indicators closely related to the LNM of CRC [20].…”
Section: Discussionsupporting
confidence: 90%
“…We found that undifferentiated carcinomas, such as signet-ring-cell carcinomas and mucinous adenocarcinomas, were associated with a high incidence of LNM. This finding was in line with those reported by previous studies indicating that patients with grade III/IV tumors have a higher rate of LNM than patients with grade I/II tumors [ 22–24 ]. Unfortunately, we were unable to extract information regarding tumor budding and lymphatic-vessel invasion from the SEER database in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, lymph node metastasis has garnered increased attention in recent years. According to previous studies, the proportion of lymph node metastasis in patients with T1-stage CRC was reported to be 5.6% and 5.5%, which is relatively low[ 11 , 12 ]. In this study, the proportion of lymph node metastasis in patients with T1-stage CRC was 8.41%.…”
Section: Discussionmentioning
confidence: 99%